2015
DOI: 10.1007/s12199-015-0473-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index and uric acid: a study on Japanese adult twins

Abstract: Objectives The present study aimed to investigate the association between body mass index (BMI) and uric acid (UA) using the twin study methodology to adjust for genetic factors. Methods The association between BMI and UA was investigated in a cross-sectional study using data from both monozygotic and dizygotic twins registered at the Osaka University Center for Twin Research and the Osaka University Graduate School of Medicine. From January 2011 to March 2014, 422 individuals participated in the health examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 41 publications
6
44
2
1
Order By: Relevance
“…Another distinct finding in our study was discovering that the highest sUA levels in this sample were detected among females in early childhood (ages 2–5). Other studies (Suzuki et al, ; Tanaka et al, ) have identified the gender‐specificity of serum uric acid in adult populations, but few among youth. One possible explanation for the high sUA levels detected in girls in early childhood (ages 2–5) is that they had significantly higher BMI percentiles than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Another distinct finding in our study was discovering that the highest sUA levels in this sample were detected among females in early childhood (ages 2–5). Other studies (Suzuki et al, ; Tanaka et al, ) have identified the gender‐specificity of serum uric acid in adult populations, but few among youth. One possible explanation for the high sUA levels detected in girls in early childhood (ages 2–5) is that they had significantly higher BMI percentiles than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between SUA and anthropometric measures of overall adiposity is well established. Several studies found cross-sectional associations between BMI or WC with SUA or hyperuricemia [26][27][28] . Moreover, SUA levels have predictive ability with respect to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not only elevated SUA concentrations were associated with the increasing risk of obesity, but obesity was also associated with higher risk of hyperuricemia. For example, Tanaka et al 26. found that BMI was significantly associated with SUA in Japanese adult twins, after adjusting for both genetic and familial environment factors.…”
Section: Discussionmentioning
confidence: 99%